Personality and Psychiatric Disorders in Women Affected by Polycystic Ovary Syndrome - Scaruffi, Elisabetta; Gambineri, Alessandra; Cattaneo, Stefania; Turra, Jenni; Vettor, Roberto; Mioni, Roberto (Frontiers in Endocrinology, 2014)
Abstract Background: Polycystic ovary syndrome (PCOS) is the most prevalent endocrine disorder among fertile women. Studies show reduced quality of life, anxiety, depression, body dissatisfaction, eating disorder and sexual dysfunction, but the etiology of these disturbs remains still debated. The aim of our study is to verify whether this hyperandrogenic syndrome characterizes a strong psycho(patho)logical personality. Method: Sixty PCOS subjects (mean age 25.8 ± 4.7 yrs) were evaluated by antropometric, metabolic, hormonal, clinical and psychological parameters. After the certainty of the diagnosis of PCOS, the Rorschach test, according to Exner's Comprehensive System (CS) and the Millon Clinical Multiaxial Inventory-III (MCMI-III) were administered to each patient. The control group, on which the comparison was carried out, was composed by 40 healthy and aged compared women who were exclusively administered the Rorschach test according to C.S. Results: MCMI-III evidenced axis II DSM-IV personality disorders (4.1% schizoid, depressive, sadistic, negativistic (passive-aggressive) and masochistic, 6.1% avoiding, 12.2% dependent, 20.4% histrionic, 16.3% narcissistic, 2.0% obsessive-compulsive) and axis I DSM-IV psychiatric disorders: 10.2% anxiety, 2.0%, somatoform disorder and bipolar disorder, 16.3% major depressive disorder. Finally we found 44.9% delusional disorder and 4.1% thought disorder. Rorschach test’s results show 53.1% reduced coping abilities and social skills, 55.1% depression, 30.6% perceptual distortion and cognitive slippage, 24.5% constantly alert and worry, 8.1% at risk for suicide and finally about 50% of our patients had chronic stress. Conclusion: PCOS women have relevant personality and psychiatric disorders, when compared with normal subjects.